Determination of Shelf Life for Sausages Produced From Some Freshwater Fish Using Two Different Smoking Methods - Ozpolat, Emine; Patir, Bahri (Wiley, 2016)
In the present study, microbiological, chemical and sensory changes of sausage samples produced from fillets of Chondrostoma regium, Luciobarbus mystaceus and Capoeta trutta implemented with traditional and liquid smoke were investigated during a storage period of 70 days at 41C. The results of microbiological, physicochemical, chemical and sensory analyses showed that there were no differences between sausages smoked with either liquid smoke or traditional smoke (P>0.05). As a result, each of the three fish species can be used in the production of sausage; there was no significant difference in terms of implementation of traditional or liquid smoke in product quality, but liquid smoke is more practical for implementation. The quality of the vacuum-packed and stored sausage samples decreased during storage, but the sausages were of satisfactory eating quality until approximately 56 days of storage. Practical ApplicationsWith this study, we determined that fish species without economic importance could be used for industrial targets by using those species as a meat resource for sausage production. We also found that liquid smoke was easy to use for sausage production and it did not have any negative effects in terms of sensory, microbiological and chemical quality of fish sausage.
Keywords: Storage Stability; Liquid Smoke; Vacuum; Anchovy; Quality; Fillets; L.